Systemic Embolization from an Unusual Intracardiac Mass in the Left Ventricular Outflow Tract - Kelechukwu U. Okoro; Timothy R. Larsen; John C. Lystash (Case Reports in Medicine)
Endocarditis can affect any endocardial surface; in the vast majority of cases, the cardiac valves are involved. It is exceedingly rare to develop infective endocarditis on the endocardium of the left ventricular outflow tract due to the high velocity of blood that traverses this area. Herein, we present a rare case of left ventricular outflow tract endocarditis that likely occurred secondary to damage to the aortic valve leaflets (from healed prior aortic valve endocarditis) causing a high velocity aortic valve regurgitant jet that impinged upon the interventricular septum which damaged the endocardium and resulted in a fibrotic “jet lesion.” This fibrous jet lesion served as a nidus for bacterial proliferation and vegetation formation. The high shear stress (due to high blood flow velocity through the left ventricular outflow tract) likely promoted the multiple embolic events observed in this case. Our patient was successfully treated with aortic valve replacement, vegetation resection, and antibiotics.